The "Art" of the Diviner: The Tablet VAT 13141 (Bab 36607) from Babylon and Two Clay Models from Ebla and Tell Tuqan - Cohen, Yoram 1968- (2022)
The purpose of this article is to elucidate some plastic representations as aids for instruction in the art of divination. We will first discuss a drawing on a tablet from Babylon, VAT 13141 (Bab 36607), and then continue with two plastic clay models, one from Ebla and the other from nearby Tell Tuqan. As will be argued, these objects have been previously misidentified in the literature, thus obscuring their objective and use.